THE ROLE OF AUDIT TENURE IN MODERATING AUDIT DELAY FACTORS - stefanny, Stefanny; Muhsin; Astarani, Juanda (Program Studi Manajemen Fakultas Ekonomi UST, 2025)
This study examines the effect of financial distress, KAP size, and profitability on audit delay, with audit tenure as a moderating variable, in energy sector companies listed on Indonesia Stock Exchange (IDX) from 2019 to 2023. Data was obtained from the financial statements of 19 main board energy sector companies during that period. The sample selection was carried out through the purposive sampling method. Data analysis used IBM SPSS 26 and hypothesis testing was carried out using a moderated regression analysis approach. The research findings show that financial distress and profitability have no significant effect on audit delay, while KAP size has a significant negative effect on audit delay. In addition, audit tenure is not proven to be able to moderate the relationship between financial distress, KAP size, or profitability on audit delay. This study contributes to the literature by exploring the role of audit tenure as a moderating variable in the effect of financial distress, KAP size, and profitability on audit delay, especially in the energy sector which is known to have a high level of audit delay.